2016
DOI: 10.18632/oncotarget.11270
|View full text |Cite
|
Sign up to set email alerts
|

The HERC2 ubiquitin ligase is essential for embryonic development and regulates motor coordination

Abstract: A mutation in the HERC2 gene has been linked to a severe neurodevelopmental disorder with similarities to the Angelman syndrome. This gene codifies a protein with ubiquitin ligase activity that regulates the activity of tumor protein p53 and is involved in important cellular processes such as DNA repair, cell cycle, cancer, and iron metabolism. Despite the critical role of HERC2 in these physiological and pathological processes, little is known about its relevance in vivo. Here, we described a mouse with targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…HERC2 is a large HECT and RCC-like domain-containing protein comprising 4834 amino acids. Mutations in the HERC2 gene have been linked to a developmental delay (23,24), and mice with homozygous truncation of the gene are not viable (25). Although HERC2 performs a range of functions with various interacting proteins, one of its major roles is the regulation of DNA replication and damage response.…”
Section: Introductionmentioning
confidence: 99%
“…HERC2 is a large HECT and RCC-like domain-containing protein comprising 4834 amino acids. Mutations in the HERC2 gene have been linked to a developmental delay (23,24), and mice with homozygous truncation of the gene are not viable (25). Although HERC2 performs a range of functions with various interacting proteins, one of its major roles is the regulation of DNA replication and damage response.…”
Section: Introductionmentioning
confidence: 99%
“…Increased DNA repair and decreased sensitivity to apoptosis may have negative consequences on normal embryonic or fetal development (Mitchell, ). Cubillos‐Rojas et al () confirmed a new function for HERC2 ubiquitin ligase as a regulator of motor coordination, and this protein is essential for embryo growth. Although there are very few studies on the effects of HERC2 on human embryo development, the existing evidence suggests that HERC2 is a promising focus for future investigations.…”
Section: Discussionmentioning
confidence: 93%
“…Proteomic analysis implicated multiple molecular pathways in HERC2 mediated neurodevelopmental phenotype including pathways involved in the morphogenesis of neurons in addition to mitochondrial and ubiquitin-proteosome pathways (Abraham et al, 2019). Functional studies suggested a role for HERC2 protein in brain synaptogenesis and motor coordination (Cubillos-Rojas et al, 2016;Valnegri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%